Hybrid Learning Model in Islamic Religious Education Based on Information Technology: A Case Study in Senior High School - Munthe, Debi; Romauli, Romauli; Maha, Lina; Yeni, Rabba (Integrasi: Jurnal Studi Islam dan Humaniora, 2025)
This study aims to describe the implementation of the hybrid learning model based on information technology (IT) in Islamic Religious Education (PAI) at Senior High School. The background of this research is the need for innovative learning that integrates face-to-face instruction with online learning, making it more flexible, effective, and relevant to the digital era. This research employed a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation involving Islamic Religious Education teachers and students at the senior high school level. The findings indicate that the hybrid learning model has a positive impact on enhancing students’ learning motivation, understanding of Islamic Education materials, and digital literacy skills. However, challenges remain, including limited technological facilities and teachers’ readiness in managing hybrid learning. This study is expected to contribute to the development of IT-based innovations in Islamic Religious Education at the senior high school level.